Death of a chocoholic - Hollis, Lee (Hollis, Lee. Hayley Powell food and cocktails mystery, 2014)
"Fed up with dating after a disastrous setup, the only thing Hayley wants to snuggle up to is a box of made to order chocolates from plus sized, plus mouthed chocolatier Bessie Winthrop. But when Bessie is found dead in her kitchen, only Hayley suspects that Bessies "heart attack" might actually be a candy coated murder. Turns out Bessie had more enemies than a boxful of chocolates, each one a suspicious flavour. Its sticky business juggling a job, two teenagers and finding a killer, but its better than letting a killer find Hayley first..."-- Back cover.